2019
DOI: 10.1016/j.ymssp.2019.04.042
|View full text |Cite
|
Sign up to set email alerts
|

Phase driven study for stochastic linear multi-dofs dynamic response

Abstract: This work addresses the computation of dynamic responses of stochastic linear systems using polynomial chaos expansion. As is now well known, polynomial chaos does not offer an accurate representation of dynamic response around resonances when the responses are evaluated for several frequency values. A new parametrization of the frequency response function is then proposed: instead of considering the frequency as the main parameter, a "total phase" parameter is defined and used to define the dynamical system t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…An intrusive PCE was implemented in the HBM process to build the nonlinear response from a limited number of runs of the computational model. Sarrouy et al [230,231] proposed to use the phase of vibration as a new control parameter in linear stochastic systems to eliminate multimodality and discontinuity in FRFs. This viewpoint may also be inspiring for solving the multi-solution issue in nonlinear systems with uncertainties although till now no relevant research has been reported to clarify how to transfer back to the frequency measure from the phase measure.…”
Section: Natural Characteristics and Unbalanced Responsesmentioning
confidence: 99%
“…An intrusive PCE was implemented in the HBM process to build the nonlinear response from a limited number of runs of the computational model. Sarrouy et al [230,231] proposed to use the phase of vibration as a new control parameter in linear stochastic systems to eliminate multimodality and discontinuity in FRFs. This viewpoint may also be inspiring for solving the multi-solution issue in nonlinear systems with uncertainties although till now no relevant research has been reported to clarify how to transfer back to the frequency measure from the phase measure.…”
Section: Natural Characteristics and Unbalanced Responsesmentioning
confidence: 99%